The Impacts of Brand Credibility, Brand Prestige, and Online Costumer Reviews on Purchasing Interest - Lusian, Nina Mardati; Harjanti, Sri (Journal of International Conference Proceedings, 2023)
This research aims to verify and analyze the impacts of brand credibility, brand prestige, and online customer reviews on purchasing interest of students at the Pembangunan Nasional "Veteran" Yogyakarta University who enjoy iPhone smartphone products. Questionnaires were distributed using nonprobability Purposive sampling techniques, and regression analysis are adopted to test the predetermined hypotheses. Results show that there are positive relations between jointly brand credibility, brand prestige, and online customer reviews on purchasing interest. Individually tested, brand credibility, brand prestige and online customers’ review have positive relation and highly significant impact on purchasing interest, respectively.